2017
DOI: 10.3126/cs.v5i1.24296
|View full text |Cite
|
Sign up to set email alerts
|

Status and trends of human-wildlife conflict: A case study of Lelep and Yamphudin region, Kanchenjunga Conservation Area, Taplejung, Nepal

Abstract: Aim Human-wildlife conflict is one of the major challenges in Kanchenjunga Conservation Area. It may erode public support in wildlife conservation. Here, we review the extent to which wildlife damages livestock and crops. Location Lelep and Yamphudin region, Kanchenjunga Conservation Area, Taplejung, Nepal Materials and methodsThe study employed a combination of surveying methods such as focus group discussion, key informant interview and field observation from 21 July to 06 August 2013. Focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…From our survey, some herders mentioned that they would expand their yak herd size to cope with losses due to predation which they mentioned has increased over the years. A similar increase of wild predation on yaks was reported in the Ghunsa valley in Nepal [46]. A few herders (n = 3) also stated that whether they keep a small or large herd size, they should look after them anyway, so they plan to expand their herd size in the next 10 years.…”
Section: Discussionmentioning
confidence: 56%
“…From our survey, some herders mentioned that they would expand their yak herd size to cope with losses due to predation which they mentioned has increased over the years. A similar increase of wild predation on yaks was reported in the Ghunsa valley in Nepal [46]. A few herders (n = 3) also stated that whether they keep a small or large herd size, they should look after them anyway, so they plan to expand their herd size in the next 10 years.…”
Section: Discussionmentioning
confidence: 56%
“…A study conducted in Kanchenjunga Conservation Area of Nepal reported that livestock depredation in Ghunsa valley, Lelep village development Committee of Taplejung district was increasing with an annual average loss rate of 11% in ten years (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) [23]. WWF [8] also reported the extent of economic loss due to crop damage by elephants and rhinos were indicating that transformation of elephant habitats to other uses (settlement, agriculture etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Household survey was supplemented by Key Informant Interviews (KII) (n=5) with community and sector forest officials (Sherchan and Bhandari, 2017;Bhattarai and Fischer, 2014 221 | P a g e to key informants contained questions related to compensation schemes that are provided for HWC victims and the role played by them in conservation of wildlife present in the area.…”
Section: Key Informant Interviewsmentioning
confidence: 99%